Role of engineering ethics in construction execution and completion - Asmawan Mohd Sarman; Elis Mardzianah Mazlan; Jazmina Bazla Jun Iskandar; Bernice Annette Hugh; Shen Ling; Wei Guomin (IDEAS, 2024)
The main objective of this paper is to analyse the current issues related to unethical behaviours in the construction industry. This research will discover the law acting on the cases of bribery, money laundering, cheating and corruption. The case study area focuses on Malaysia construction industry. Suggestions and recommendations are addressed in preventing unethical behavior from occurring. This paper is a comprehensive review paper where several past papers, journals, articles, newspapers and websites were analysed to collect information on the case topic. Databases such as Google Scholar, Scopus, IEEE, and Science Direct were used as primary sources. The paper presents the latest cases relating to unethical behaviour in the construction industry including, engineers, project managers and project directors between the years 2017 to 2023. The effect of the unethical behaviour was also discussed and explained in three different aspects which are individual, organization and nation. Lastly, three (3) recommendations for encountering immoral behaviour in the construction industry were clearly stated which are Reporting Suspicious Transaction, Internal Audit, and Whistle-blowing system. As a result, this paper has successfully proven that engineering ethics plays a significant role in construction execution and completion. This paper analysed 48 papers from reliable sources to prove the role of engineering ethics in construction execution and completion.